ERKIN VOHIDOV LIRIKASIDA G’OYA VA ADABIY TALQIN - Sh.Baltayeva, Z. (SCIENCE and SOCIETY, 2021)
The articles deals with E.Vokhidov’s development of ideas and literacy interpretation, poet’s peculiarities of expression style and artistic work of words. In the article, the presentation of artist’s indulgence , an image object level, the principles of poetic study of life, the nature of aesthetic perception, author’s skills aspects and evaluation criteria are theatrically summarized.
Keywords: lyrics; literary interpretation; poetical standpoint; methodological research; artistic essence; logical sequence; imagination; emotion; spirit image